Analisis Profil dan Penerapannya Pada Suatu Telaah Produksi Kapulaga di Sumatera Barat - Zainuriadi Zainuriadi; Helma Helma (Journal of Mathematics UNP, 2023)
Cardamom is one of the potential commodities in the international market. Cardamom is a valuable spice plant that can be used in various ways, where the price of dried cardamom is among Rp.90,000 to Rp.110,000 per kilogram. According to horticultural fixed figures, the harvested area of cardamom increased to 857,190 hectares in 2000-2006 and then decreased to 541,290 hectares from 2007-2010.Therefore, a comparison of productive land area with the amount of cardamom production in West Sumatra is needed using profile analysis. The profile analysis compared the average land area values of cardamom production and production using parallel tests, squeezed tests and level tests. The results obtained are the average area of productive land and the amount of production in the districts of Padang Pariaman, Agam, Lima Puluh Kota, Pasaman, West Pasaman, Padang City, Padang Panjang, Bukit Tinggi and Payakumbuh aligned, squeezed and level, so it can be said that the use of productive land in the area is optimal.